Regulation of gastrulation in Drosophila - Leptin, Maria (Henry Stewart Talks, 2008)
Events during gastrulation and mesoderm cell invagination, Cell shape changes, Genes acting upstream of mesodermal invagination, Search for genes controlling mesoderm cell shape changes, The role of cell division, The importance of apical concentration of cytoskeletal regulators, and proteins mediating their apical concentration
Archived at 2021/02/25